Neutrophil to lymphocyte ratio and clinical outcomes in COPD: recent evidence and future perspectives. (7th February 2018) - Paliogiannis, Panagiotis; Fois, Alessandro G.; Sotgia, Salvatore; Mangoni, Arduino A.; Zinellu, Elisabetta; Pirina, Pietro; Negri, Silvia; Carru, Ciriaco; Zinellu, Angelo
Chronic obstructive pulmonary disease (COPD) is a disabling condition that is characterised by poorly reversible airflow limitation and inflammation. Acute exacerbations of COPD are a common cause of hospitalisation and death among COPD patients. Several biochemical markers have been studied as outcome predictors in COPD; however, their measurement often requires significant time and resources. Relatively simple biomarkers of inflammation calculated from routine complete blood count tests, such as the neutrophil to lymphocyte ratio (NLR), might also predict COPD progression and outcomes. This review discusses the available evidence from studies investigating the associations between the NLR, COPD exacerbations and death in this patient group. Blood neutrophil to lymphocyte ratio can predict stable COPD, its exacerbations and prognosis http://ow.ly/2aJ030hzUIn